Ethnobotany of Pelleng, a Pakpak Batak Spiced Rice from Bakal Julu Community, and Its Application in Biology Learning through Educational Posters - Rivaldi Sitinjak; Marina Silalahi; Fajar Adinugraha (Borneo Journal of Biology Education (BJBE), 2025)
Traditional food, Pelleng, is a spiced rice dish served during the traditional ceremonies of the Pakpak Batak community in North Sumatra, symbolizing strength, blessing, and unity. One of its main ingredients is Andaliman (Zanthoxylum acanthopodium), an endemic spice of the Toba Highlands known for its distinctive flavor, ecological value, and cultural significance. Despite its rich heritage, no prior studies have documented the ethnobotanical composition of Pelleng or linked it to biodiversity learning. Therefore, this study aims to identify the plant species used as spices in preparing Pelleng rice and to explore their cultural and symbolic meanings within the Pakpak Batak community., interpret their cultural meanings, and make an educational poster connecting traditional food heritage with Grade X biodiversity topics. Field exploration and surveys were conducted in Bakal Julu Village, Siempat Nempu Hulu Subdistrict, Dairi Regency, using semi-structured interviews with four key informants (traditional leaders, traditional cooks, elders, and homemakers), complemented by field surveys and photographic documentation. Data were analyzed qualitatively and descriptively to determine the ecological and cultural values of each species. The study identified 17 plant species from 11 families used as spices in Pelleng preparation, including food crops, spices, and medicinal plants. Andaliman emerged as a cultural keystone species whose sensory and symbolic roles are irreplaceable. Integrating Pelleng’s ethnobotanical knowledge into instructional media—such as a thematic biodiversity poster—offers a meaningful approach to bridging indigenous knowledge and science education. This research is expected to enrich biology teaching materials with culturally relevant content, raise students’ awareness of biodiversity, and support the preservation of cultural heritage through the documentation and educational integration of ethnobotanical knowledge.